Kelestarian Bandar Kecil Wilayah Lembah Bernam Dari Perspektif Kesejahteraan Penduduk: Small Towns Sustainability In Bernam Valley From Human Welfare Perspectives - Saleh, Yazid; Mahat, Hanifah; Hashim, Mohmadisa; Nayan, Nasir (GEOGRAFI, 2015)
This study aimed to investigate the sustainability of the population in Bernam Valley region from welfare perspective. The scope of human welfare of this study was to investigate the level of the relationship and the influence of social sustainability, economic sustainability and environmental sustainability. Using questionnaires as research instrument, a total of 800 heads of households were sampled using selected random sampling methods in eight selected small towns. Every data were analysed using descriptive and inference (correlation and regression) analysis. Result shows that sustainability level of small towns for all variables were at moderate level. All variables clearly show a significant and positive relationship. Regression analysis shows that social welfare had a great impact on the well-being, followed by economic prosperity and welfare of the environment. It can be concluded that the well-being of the population which includes all three components of social sustainability, economic sustainability and the preservation of the environment must be addressed. Even major manifestations of developmental functions were received by small towns in the context of sustainability for the benefit of the population into the national agenda.